Pengambilan Keputusan Pembelian Kue Pisang Berdasarkan Komunikasi Pemasaran, Inovasi Produk, dan Harga - Ida Rosada; Nurliani; A. Asrarul Amri; Akda Saktiyandi Asrul (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2025)
Rapid business development has given rise to tight market competition. Every day business people appear to introduce products with new creativity and innovation. One of the snacks offered on the market is brownies with the brand